First European case of Creutzfeldt-Jakob disease with a PRNP G114V mutation. (August 2019) - Cousyn, Louis; Grabli, David; Seilhean, Danielle; Azuar, Carole; Huiban, Camille; Epelbaum, Stéphane; Bouaziz-Amar, Elodie; Brandel, Jean-Philippe; Galanaud, Damien; Méneret, Aurélie
Abstract: Genetic Creutzfeldt-Jakob disease is due to mutations in the PRNP gene. Only two families with a PRNP G114V mutation have been described around the world. We report the first European case, who had no family history and initially presented with isolated deficit in hippocampus-dependent memory. Initial investigations were normal except for elevated total tau protein in the cerebrospinal fluid. He died 4 years after disease onset. This case highlights the diagnostic difficulties posed by genetic Creutzfeldt-Jakob disease, and shows that genetic analyses should be considered even in sporadic cases.